Asap Cair Kayu Sengon sebagai Chelating Agents Logam Timbal (Pb) pada Model Menggunakan Biji Kedelai (Glycine max) - A'yuni, Nur Rohmah Lufti; Darmadji, Purnama; Pranoto, Yudi (Universitas Muhammadiyah Yogyakarta, 2017)
Soybean (Glycine max) is one of the plants that strongly accumulate heavy metals. Therefore, soybeans need to be given a pre-treatment so that no accumulation of heavy metals in the human body. The aim of this study was to determine the influence of Paraserianthes falcataria (L.) Nielsen wood liquid smoke concentration to the reduction of Pb metal in soybean seeds and determine the influence of liquid smoke compounds to the reduction of Pb metal in soybean seeds. The study used a completely randomized design with three replications. Factor to be examined was the effect of liquid smoke concentration to the reduction of Pb metal in soybean seeds with variations 0; 12.5; 25; 50 and 100 % by 25 ml. Parameters measured were Pb metal reduction, the changes of acid, phenol, carbonyl and pH liquid smoke after chelation and Pb metal reduction because of liquid smoke compounds. Model of Pb metal was made from soybean seeds that have been contaminated by Pb (NO3) 2 with the 2 ppm concentration. The results showed that the greater the concentration of liquid smoke, the greater the reduction of Pb metal. The liquid smoke with the 100% concentration gives the highest reduction of Pb metal in soybean seeds 59.12%. Carbonyl compounds of liquid smoke give the highest reduction of Pb metal in soybeans seeds 46.42Â %, followed by acetic acid 43.97 % and phenol 41.55 %.